Role of Water in the Dynamic Crystallization of CuTCNQ for Enhanced Redox Catalysis (TCNQ = Tetracyanoquinodimethane). Issue 15 (5th July 2017) - Siu, Mark C.; Anderson, Samuel R.; Mohammadtaheri, Mahsa; Ahmed, Taimur; Walia, Sumeet; Ramanathan, Rajesh; Bansal, Vipul
Abstract : A new bisolvent approach is introduced to overcome the limitation of wet chemical routes of a semiconducting phase I CuTCNQ (7, 7, 8, 8‐tetracyanoquinodimethane) synthesis, which currently does not allow these materials to be grown beyond certain dimensions (10–15 µm). The use of water as a cosolvent during acetonitrile‐mediated conventional synthesis of CuTCNQ allows a dynamic control over its crystallization and dissolution process through favorably shifting the reaction equilibrium. This enables CuTCNQ structures of unique morphologies with secondary growth, alongside dimensions exceeding 100 µm to be produced. These new morphologies of phase I CuTCNQ show remarkable promise in redox catalysis over their conventional counterparts by facilitating efficient charge transfer at the catalyst–reactant interface. As catalytic, sensing, and electronic performance of materials strongly depend upon their morphological characteristics, the concepts introduced here have potential applicability for controllable fabrication of a range of metal‐organic charge transfer complexes of technological importance. Abstract : The challenge in fabrication of large dimension CuTCNQ (7, 7, 8, 8‐Tetracyanoquinodimethane) organic charge transfer complexes is overcome. The reported bisolvent strategy allows a dynamic control over competing CuTCNQ crystallization and dissolution processes. This enables growth of CuTCNQ exceeding 100 µm in length with secondary structures. This new material acts as an outstanding redox catalyst.